2008
DOI: 10.1186/1471-2393-8-40
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol in addition to routine treatment of postpartum hemorrhage: A hospital-based randomized-controlled trial in Karachi, Pakistan

Abstract: Background: Postpartum hemorrhage (PPH) remains a major killer of women worldwide. Standard uterotonic treatments used to control postpartum bleeding do not always work and are not always available. Misoprostol's potential as a treatment option for PPH is increasingly known, but its use remains ad hoc and available evidence does not support the safety or efficacy of one particular regimen. This study aimed to determine the adjunct benefit of misoprostol when combined with standard oxytocics for PPH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 20 publications
2
36
1
Order By: Relevance
“…In addition, approximately 5% of women bled ≥350 ml in secondary prevention clusters, which is lower than the 25% hypothesised based on prior studies 13. The reasons for the low levels of bleeding in this study are unclear, although other studies document low or declining measured ‘PPH rates’ during study recruitment, thought to be due to increased provider confidence and training 21, 22, 23, 24, 25. In compliance with government policy, ANMs referred high‐risk deliveries to higher‐level facilities, and women enrolled may have constituted a low‐risk population, although numerous studies have shown that it is difficult to identify the majority of women who will experience PPH based on pre‐existing risk factors.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, approximately 5% of women bled ≥350 ml in secondary prevention clusters, which is lower than the 25% hypothesised based on prior studies 13. The reasons for the low levels of bleeding in this study are unclear, although other studies document low or declining measured ‘PPH rates’ during study recruitment, thought to be due to increased provider confidence and training 21, 22, 23, 24, 25. In compliance with government policy, ANMs referred high‐risk deliveries to higher‐level facilities, and women enrolled may have constituted a low‐risk population, although numerous studies have shown that it is difficult to identify the majority of women who will experience PPH based on pre‐existing risk factors.…”
Section: Discussionmentioning
confidence: 50%
“…The three published trials (31)(32)(33) were relatively small, with a total of 465 women participating. The unpublished WHO-Gynuity trial (34) included 1400 women in Argentina, Egypt, South Africa, Thailand and Viet Nam.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…The unpublished WHO-Gynuity trial (34) included 1400 women in Argentina, Egypt, South Africa, Thailand and Viet Nam. In three trials (31,33,34), 600 µg of misoprostol was administered orally or sublingually, while in the fourth trial (32) 1000 µg was administered orally, sublingually or rectally. The results of the WHO-Gynuity trial (34) were presented to the Consultation and are included in the GRADE table (page 28, GRADE Table B1).…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Since 1987, misoprostol has been used to prevent or treat PPH in doses up to 600 µg in oral or sublingual administration [8][9][10] and up to 1000 µg rectally [11][12][13][14][15][16]. Misoprostol tablet can also be absorbed by both rectal and vaginal routes [17].…”
Section: Introductionmentioning
confidence: 99%